The Effect of Different Solvents on the Content of Black Cumin Seed Extract (Nigella sativa) - Hariutami, Desi; Darmawati, Sri; Permana, Atna; Zuraida, Zuraida (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2024)
Seeds of black cumin (Nigella sativa L.), also called